Cooperative Model with Baurus Pattern Problem Solving to Improve Students' Collaborative Skills - Dixiyei, Andreas; Keliat, Natalia Rosa; Cahyaningrum, Desti Christian (PEDAGOGIA, 2024)
This research aims to determine the effect of the cooperative learning model with Baurus pattern problem solving method on the collaborative skills of students of SMP Kristen 2 (Christian Junior High School 2) on the subject of Indonesian Ecology and Biodiversity. The method used in this research is quantitative descriptive (quasi-experimental). The research subjects were students of class VII-D (control class) and class VII-C (experimental class) at SMP Kristen 2 Salatiga. Data analysis is carried out using inferential statistics with the Wilcoxon test, Man Whitney, and N-Gain score. The results of the validity and reliability test on the research instrument show that the instrument is valid and reliable. Based on the results of observations, the syntax of the cooperative learning model with Baurus pattern problem solving method is included in the fully implemented category with a score of 4.9. Students also give positive response with a score of 0.9. The results of the Wilcoxon test show that the cooperative learning model with Baurus problem solving method has an effect on collaborative skills with a p-value of 0.00 α 0.05 and an N-Gain score reaching 0.7 (high). The results of the Man Whitney test show a p-value of 0.00α0.05, which means there is a significant difference in influence between the cooperative learning model with Baurus pattern problem solving method and STAD cooperative learning model.